Effect of cropyear on the different agrotechnical parameters and yield of asparagus (Asparagus officinalis L.) - Erdős, Zsuzsa (Acta Agraria Debreceniensis, 2015)
The experiments were performed in the University of Debrecen Centre fog Agricultural Research Institute of Nyíregyháza of 1500 m2 asparagus plantation in 2011. We were determine the number of shoots, plant height, fold thickness and yield of asparagus hybrids. I observe in the effects of three different asparagus genotypes (Vitale, Cumulus, Grolim) growth and development of the data sets are required. Compared to previous years, the year 2014 was also an unusually warm and rainy weather, which makes the plantation produced outstanding development. Effect of the early warming, this year the harvest was to begin one month then in 2013.